PENETAPAN NISBAH BAGI HASIL PADA AKAD KERJASAMA PEMELIHARAAN HEWAN TERNAK PERSPEKTIF EKONOMI SYARIAH - Yarmunida, Miti; Wulandari, Wulandari (Institut Agama Islam Bengkulu, 2016)
Determining the profit-sharing ratio in Islamic concepts is a necessity. The system of determination of the profit-sharing ratio should refer to the principle of fairness of inter-personal balance of the conduct of the council. The behavior of the Muslim community in Indonesia, especially in the villages, is still a lot that does not set the profit-sharing ratio at the time of agreement (akad). As with the livestock raising, the yield-sharing system is set at the time of the outcome and often the determinant of how much of each part is the owner of the livestock. The unilateral provision makes one party feel unfair and is forced to accept his part. Keywords: Nisbah Profit-Sharing, CoorporationÂ Agreemen